Influence of land cover change on atmospheric organic gases, aerosols, and radiative effects - R. Vella; R. Vella; M. Forrest; A. Pozzer; A. Pozzer; A. P. Tsimpidi; T. Hickler; T. Hickler; J. Lelieveld; J. Lelieveld; H. Tost (Atmospheric Chemistry and Physics)
Biogenic volatile organic compounds (BVOCs) are emitted in large quantities from the terrestrial biosphere and play a significant role in atmospheric gaseous and aerosol compositions. Secondary organic aerosols (SOAs) resulting from BVOC oxidation affect the radiation budget both directly, through the scattering and absorption of sunlight, and indirectly, by modifying cloud properties. Human activities have extensively altered natural vegetation cover, primarily by converting forests into agricultural land. In this work, a global atmospheric chemistry–climate model, coupled with a dynamic global vegetation model, was employed to study the impacts of perturbing the biosphere through human-induced land use change, thereby exploring changes in BVOC emissions and the atmospheric aerosol burden. A land use scheme was implemented to constrain tree plant functional type (PFT) cover based on land transformation fraction maps from the year 2015. Two scenarios were evaluated: (1) one comparing present-day land cover, which includes areas deforested for crops and grazing land, with potential natural vegetation (PNV) cover simulated by the model, and (2) an extreme reforestation scenario in which present-day grazing land is restored to natural vegetation levels. We find that, compared to the PNV scenario, present-day deforestation results in a 26 % reduction in BVOC emissions, which decreases the global biogenic SOA (bSOA) burden by 0.16 Tg (a decrease of 29 %), while the total organic aerosol (OA) burden decreases by 0.17 Tg (a reduction of 9 %). On the other hand, the extreme reforestation scenario, compared to present-day land cover, suggests an increase in BVOC emissions of 22 %, which increases the bSOA burden by 0.11 Tg and the total OA burden by 0.12 Tg – increases of 26 % and 6 %, respectively. For the present-day deforestation scenario, we estimate a positive total radiative effect (aerosol + cloud) of 60.4 mW m−2 (warming) relative to the natural vegetation scenario, while for the extreme reforestation scenario, we report a negative (cooling) effect of 38.2 mW m−2 relative to current vegetation cover.